MEKANISME PENGATURAN SISTIM SARAF PADA TUBUH IKAN DI LINGKUNGAN PERAIRAN YANG TERKONTAMINASI OLEH SIANIDA - Achyani, Ratno (Jurnal Harpodon Borneo, 2011)
Fish and invertebrate aquatic animals are very sensitive to cyanide exposure. Free concentration in the environment can reduce the ability to swim and inhibit reproduction of many species of fish. Another adverse effect is pathology, sensitivity the nature of predators, impaired respiratory system, disorders of osmoregulation and different growth patterns. The networks that depend anaerobic respiration, such as primary liver and nervous system was also affected. Fundamental changes where associated with toxin by hydrogen cyanide (HCN) is distinguished in three categories, the sensors, motor and interneuronal depends on how much damage is take. HCN may cause cell death or survival but there is damage in small sections of dendrites or axons, so that shrinkage or loss of entire functions. In fish it will lose swimming ability for a moment, and when in large doses cause of death. Keywords : Cyanide, effect on fish, sensor, motor, interneuronal